2014
DOI: 10.1039/c4ib00035h
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neurons and osteoblasts: close partners in a microfluidic platform

Abstract: Innervation has proven to be critical in bone homeostasis/regeneration due to the effect of soluble factors, produced by nerve fibers, associated with changes in the activity of bone cells. Thus, in this study, we have established and characterized a coculture system comprising sensory neurons and osteoblasts to mimic the in vivo scenario where nerve fibers can be found in a bone microenvironment. Embryonic or adult primary dorsal root ganglion (DRG) and MC3T3-E1 osteoblastic cells were cocultured in compartme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 43 publications
0
56
0
Order By: Relevance
“…Quantification of the axonal outgrowth was performed using a MATLAB (The MathWorks Inc., Natick, MA) script named AxoFluidic 58 . This computational tool calculates the axonal networks density as a function of the distance (x-axis) to the microgrooves termination in the microfluidic chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of the axonal outgrowth was performed using a MATLAB (The MathWorks Inc., Natick, MA) script named AxoFluidic 58 . This computational tool calculates the axonal networks density as a function of the distance (x-axis) to the microgrooves termination in the microfluidic chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Preceding studies have demonstrated close membrane contact and synaptic structure in cocultures comprising DRG‐derived sensory neurons and osteoblasts, by electron microscopy analysis . Immunoreactivity to synapsin, a synaptic‐related protein, has also been observed in nerve fibers attached to osteoblasts . These results suggest that direct signal transduction from sensory neurons to osteoblasts occurs via exocytosis of glutamate or substance P. In most peptidergic sensory neurons, substance P is coexpressed with CGRP .…”
Section: Discussionmentioning
confidence: 94%
“…2A,B). Preceding studies have demonstrated close membrane contact and synaptic structure in cocultures comprising DRG-derived sensory neurons and osteoblasts, by electron microscopy analysis [32,40]. Immunoreactivity to synapsin, a synaptic-related protein, has also been observed in nerve fibers attached to osteoblasts [40].…”
Section: Discussionmentioning
confidence: 99%
“…Microfluidic chambers had an appropriate microchannel spacing for compartmentalization and probing of axonal activity. Microfluidic chambers were also adapted by adding an extra smaller reservoir (Ø 3 mm), which allowed the seeding of the DRG in a central position to the electrode matrix (Neto et al, 2014). μEF devices were composed of two separate compartments connected by 16 microchannels of 700 μm length × 9.6 μm height × 10 μm width.…”
Section: Methodsmentioning
confidence: 99%